2018
DOI: 10.5424/sjar/2018162-11813
|View full text |Cite
|
Sign up to set email alerts
|

The profitability of value-added products in dairy farm diversification initiatives

Abstract: A more open and competitive dairy market has encouraged certain dairy farms to adopt value-adding strategies in order to achieve a higher profitability, which may be important for farms’ survival. This paper investigated the role of some product characteristics in the profitability of value-added products in these farms. For this purpose, we used a unique database of 265 different products commercialized by 49 Spanish dairy farms that offers information on nine attributes of each product. Using hedonic models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
6
1
1
Order By: Relevance
“…We also found that a greater share of family labor is negatively associated with efficiency. This result seems to contradict previous studies [56], which found that family businesses seem to perform better. Our result may reflect the need to hire external workers in order to be able to achieve a greater volume of sales and thereby take greater advantage of the investment in machinery and facilities.…”
Section: Discussioncontrasting
confidence: 98%
“…We also found that a greater share of family labor is negatively associated with efficiency. This result seems to contradict previous studies [56], which found that family businesses seem to perform better. Our result may reflect the need to hire external workers in order to be able to achieve a greater volume of sales and thereby take greater advantage of the investment in machinery and facilities.…”
Section: Discussioncontrasting
confidence: 98%
“…Several authors agree that a direct marketing channel turns out to be more profitable than one with a higher degree of intermediation (Gokkaya et al, 2016;Alvarez, García-Cornejo, Pérez-Méndez, & Roibás, 2018;Naglova, Boberova, Horakova, & Smutka, 2017;Santos-Lavalle et al, 2018). One aspect to note, is that intermediaries have the ability to link and influence several actors within the distribution network (Rendón-Rendón et al, 2019), therefore, there are producers who sell only or mostly to distributors.…”
Section: Los Artículos Que Describen Casos De Intermediarismo Se Encuentran Clasifi-mentioning
confidence: 99%
“…Varios autores coinciden en que un canal de comercialización directo resulta ser más rentable que uno con mayor grado de intermediación (Gokkaya et al, 2016;Alvarez, García-Cornejo, Pérez-Méndez, & Roibás, 2018;Naglova, Boberova, Horakova, & Smutka, 2017;Santos-Lavalle et al, 2018). Un aspecto que cabe señalar, es que los intermediarios tienen la capacidad de vincular e influenciar a varios actores dentro de la red de distribución (Rendón-Rendón et al, 2019), por lo tanto, hay productores que venden solo o mayormente a distribuidores.…”
Section: Differentiation Strategyunclassified
“…If the groups are to survive and flourish, it is time that dairy groups adopted a strategy for rapid growth, emphasizing on dairy product diversification and targeting a wide range of customers. Diversification is a tried and trusted strategy that has helped all types of businesses to minimize risks and survive in the competing environments [13,25]. Livelihood diversification increases income [26] and improves livelihood security [27,28].…”
Section: Number Of Respondents Interviewedmentioning
confidence: 99%